A Commentary on Salmonella From a Pre-Harvest Perspective - Edrington, Tom S.; Brown, Tyson R. (Frontiers in Animal Science, 2022)
Salmonella occurs in all the major meat producing livestock species (ruminants, swine and poultry), most often residing within the gastrointestinal tract asymptomatically. While considerable success has been achieved post-harvest, the design of effective pre-harvest interventions to control Salmonella has lagged. A simplistic view of the extremely complex host/pathogen interaction suggests that the pathogen has a vested interest in not causing illness or death to the host. The former would initiate an immune response from the host and/or the application of therapeutic antibacterial agents, while the latter would require finding another suitable host. Due to the widespread prevalence of Salmonella within livestock and poultry, and the relatively few salmonellosis cases in comparison, it appears, and is supported by new research, that Salmonella has developed methods to avoid detection by the animal’s immune system and live essentially as a commensal organism within the gastrointestinal tract of the animal. Yet, for reasons that are not fully understood, this “commensal” Salmonella does on occasion become virulent, in young and mature animals alike. Indeed, these researchers have documented Salmonella carriage throughout the year in cattle, but only rarely, if at all, was salmonellosis observed. Further, evaluation of Salmonella isolates (serotype and antimicrobial resistance patterns) from sick and healthy cattle failed to explain that while Salmonella was present in the majority of cattle sampled on that farm, only a few developed salmonellosis. Virulence, as well as multi-drug resistance, in both livestock and humans appears to cluster within a few serotypes. As a result, petitions are circulating calling for the labeling of some Salmonella serotypes as adulterants, as was done with Escherichia coli O157:H7 and other enterohemorrhagic E. coli strains. Regulators are considering approaching the Salmonella problem by serotype, such as focusing specifically on the top 10 reported serotypes causing human illness. Herein, the authors will discuss the many challenges of controlling Salmonella pre-harvest, reflecting on the significant research portfolio that has been generated over the last 25 years, as well as challenging existing paradigms surrounding this pathogen and the experimental methods used to further our understanding of Salmonella and/or evaluate methods of control.